2019
DOI: 10.3390/su11236616
|View full text |Cite
|
Sign up to set email alerts
|

Green Supplier Evaluation and Selection with an Extended MABAC Method Under the Heterogeneous Information Environment

Abstract: With the increasing awareness of global environmental protection, green production has become a significant part for enterprises to remain in a competitive position. For a manufacturing company, selecting the most suitable green supplier plays an important role in enhancing its green production performance. In this paper, we develop a new green supplier evaluation and selection model through the combination of heterogeneous criteria information and an extended multi-attributive border approximation area compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Wei et al [30] defined the uncertain probabilistic linguistic MABAC method. Xu, Shi, Zhang, and Liu [31] designed the MABAC with heterogeneous criteria information. Liang, He, Wang, Chen, and Li [1] put forward some novel distance measures of IFSs and combined them with the MABAC method to tackle MCGDM issues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wei et al [30] defined the uncertain probabilistic linguistic MABAC method. Xu, Shi, Zhang, and Liu [31] designed the MABAC with heterogeneous criteria information. Liang, He, Wang, Chen, and Li [1] put forward some novel distance measures of IFSs and combined them with the MABAC method to tackle MCGDM issues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Xu et al [45] established an extended EDAS model with single-valued complex neutrosophic sets and applied it for green supplier selection. Xu et al [46] developed a GSES model through the combination of heterogeneous criteria information and an extended multiattributive border approximation area comparison (MABAC) method. A soft computing approach based on Mathematical Problems in Engineering [47] for the green supplier selection problem.…”
Section: Distance-based Methodsmentioning
confidence: 99%
“…Direct given [20,45,46,56,77,78,153] Expert judgement [22-26, 39, 42, 43, 47, 49, 68, 69, 74, 112, 115, 116, 123, 124, 126, 127, 135, 136, 140, 152, 156-158, 161, 166, 167, 172, 173, 182, 183, 209] 35 AHP [20, 50, 51, 72, 81-85, 125, 164, 168, 178-181, 187-193] 23 ANP [21,41,52,[86][87][88][89][90][97][98][99] 11 BWM [17-19, 48, 58, 114, 142, 184, 193, 194] 10 QFD [29,57,149,195 [34,131] Entropy method and divergence measure method [132] Expert judgement and maximizing distance method [33] Expert judgement and maximizing deviation method [118] Expert judgement and statistical variance method [31] Direct given and ordered weight [147] Table 4: Green supplier evaluation methods used in the literature.…”
Section: Subjective Weighting Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quan et al [3] designed a hybrid method for the assessment of SSS problem. Further, Xu et al [84] evaluated the green supplier selection problem by employing an extended Multi-Attributive Border Approximation area Comparison (MABAC) approach. Meksavang et al [4] suggested a modified VIKOR technique to assess the SSS problem under Picture Fuzzy Sets (PFSs) context.…”
Section: Sustainable Supplier Selection (Sss)mentioning
confidence: 99%